2001
DOI: 10.1067/mva.2001.111682
|View full text |Cite
|
Sign up to set email alerts
|

Concerns for the durability of the proximal abdominal aortic aneurysm endograft fixation from a 2-year and 3-year longitudinal computed tomography angiography study

Abstract: A continuous aortic enlargement of approximately 1 mm/y at the level of the proximal endovascular anastomosis was found. Because of the practice of oversizing the endograft relative to the infrarenal aortic neck, a loss of the endovascular seal may not become apparent until several years after endovascular abdominal aortic aneurysm repair is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 10 publications
2
76
0
2
Order By: Relevance
“…Others reported similar results and raised similar concerns. 2,[7][8][9]12,17 Our results expand on these findings and concerns. In our series, the procedural time and blood loss as well as the perioperative death rate (8.5%) were higher than in most other reports.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Others reported similar results and raised similar concerns. 2,[7][8][9]12,17 Our results expand on these findings and concerns. In our series, the procedural time and blood loss as well as the perioperative death rate (8.5%) were higher than in most other reports.…”
Section: Discussionsupporting
confidence: 77%
“…Similar concerns have also been raised by others. 2,[7][8][9]12,17,18 In the present study, we analyzed the durability and late complications after EVG repair of AAAs at our institution, where we first used an EVG to treat an AAA in November 1992. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The suprarenal and infrarenal levels have already been defined [3,8,9,10]. The infrarenal neck dilatation occurs in 21-23% of patients 2-3 years after treatment [8,9], whereas the suprarenal neck enlargement seems to be less frequent [3,5,11,12].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, many authors have shown that oversizing is positively correlated with neck dilatation [25,28,31,33,[36][37][38].…”
Section: Biomechanics and Vessel Remodelingmentioning
confidence: 99%